Investigation method of borehole collapse with the multi-field coupled model during drilling in clayey silt hydrate reservoirs - Qingchao Li; Yuanfang Cheng; Qiang Li; Fuling Wang; Chuang Zhang; Chuanliang Yan (Fracture and Structural Integrity)
The global reserves of natural gas hydrates are extremely abundant, which is attracting more and more scientists’ attention. However, hydrate reservoirs are usually clayey silt hydrate reservoirs with low strength, borehole collapse is a key issue during the drilling operation in these clayey silt hydrate reservoirs in the South China Sea. Therefore, investigation method exploration of borehole collapse simulation for wellbores drilled in hydrate-bearing sediments is of great importance for safely and efficiently developing hydrate in deep water. The finite element model coupled seepage, deformation and heat transfer is developed, and borehole collapse investigation during the overbalanced drilling operation in hydrate-bearing sediment is carried out. The results show that changes in temperature and/or pore pressure do not necessarily lead to the hydrate dissociation. For the investigation case, the temperature front reaches to the position of 35.72 cm from borehole within the near-wellbore area when the drilling operation lasted for 3 hours, but hydrate only dissociates for 17.94cm from the borehole, which is smaller than the temperature disturbance distance. Moreover, the applicability of the investigation method developed herein is verified by comparing the equivalent plastic strains obtained by the coupled model developed in this paper and the simplified model (which neglects the seepage and the heat transfer) respectively. All these results demonstrate that both the investigation method and the finite element model can be used for borehole stability simulation in hydrate-bearing sediments.